Analisis Prilaku Organisasi dan Pengaruhnya Terhadap Kinerja Pegawai Di Lembaga Pendidikan - Azhar, Imam; Nur Hakim (MADINAH, 2020)
Most of the educational organizations seek many ways to survive in today's competitive environment. In doing so, In today’s era each organization is aimed to be competitive as well through having best human resources to achieve these organizations need to support their employees. Due to this, this study aims to investigate the influence of organizational commitment, job satisfaction and job discipline towards employees’ performances. It has been discovered through previous literature that organizational commitment is defined as the relative strength of an individual’s recognition with, and participation in, an organization. The concept of the job satisfaction consists of the feelings and attitudes one has about one’s job. These attitudes include all aspects of negative or positive feelings about a particular job wihc are likely to contribute to the development of feelings of satisfaction (or dissatisfaction), while job discipline is an effort of the management of the institution to implement or execute the rules or regulations that must be adhered by all employees without exception. The data was collected from 58 employess working in different educational institutions using stratified random sampling and used path analysis. The risults of the study shown that organizational commitment has positive direct effect toward employees’ performance (0,658), job satisfaction has positive direct effect toward employees’ performance (0,162), and job discipline has positive direct effect toward employees’ performance (0,658). However, job satisfaction through organizational commitment has no positive direct effect on employees’ performance.